O noante na perda rememorada: uma leitura da melancolia em Fazes-me falta, de Inês Pedrosa - Lindini, Sidney Prando (Universidade Federal de São Carlos, 2025)
This Undergraduate Thesis, based on the novel Fazes-me Falta by the Portuguese writer Inês Pedrosa, aims to propose an analysis of the persistent behavior of mnemonic recollection as a mitigating factor in the male character’s melancholic condition in the face of losing his loved one. The objective of this study is to examine the construction of melancholy and its painful affliction as experienced by the one who remains, resulting from the constant effort to return to the past in order to remember the lost object—his friend. In this regard, the investigation will be grounded primarily on Paul Ricoeur’s “Memória, Historia, Esquecimento” and Sigmund Freud’s “Luto e Melancolia”. In a second moment, through a reading of the novel situated within the broader context of contemporary Portuguese fiction, this study intends to reflect on the role of memory in thinking about the Colonial Wars in Africa and Salazarism, based on the features of the melancholic subject and the notion of trauma, observing how the mimetic image of a decaying Portuguese citizen is mirrored in this character. This reflective exercise of considering the real within contemporary fiction leads us to focus our attention on the novel’s fragmentary construction, drawing on guiding texts such as Linda Hutcheon’s A Poetics of Postmodernism. Overall, this thesis seeks to reflect on memory and its functioning within the fictional narrative.
The nocte in remembered loss: a reading of melancholy in Fazes-me falta by Inês Pedrosa
Keywords: Melancolia; Memória; Romance Português; Trauma; Melancholy; Memory; Portuguese Novel; Trauma; LINGUISTICA, LETRAS E ARTES::LETRAS::OUTRAS LITERATURAS VERNACULAS; 16. Paz, Justiça e Instituições Eficazes